2022
DOI: 10.3390/foods11182806
|View full text |Cite
|
Sign up to set email alerts
|

Research Progresses on the Physiological and Pharmacological Benefits of Microalgae-Derived Biomolecules

Abstract: Microalgae are a kind of photoautotrophic microorganism, which are small, fast in their growth rate, and widely distributed in seawater and freshwater. They have strong adaptability to diverse environmental conditions and contain various nutrients. Many scholars have suggested that microalgae can be considered as a new food source, which should be developed extensively. More importantly, in addition to containing nutrients, microalgae are able to produce a great number of active compounds such as long-chain un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 93 publications
(80 reference statements)
0
2
0
Order By: Relevance
“…[10,11] Microalgae are considered a high-quality nutritional source for human health due to their abundant primary and secondary bioactive metabolites, such as polypeptides, lipids, vitamin polyunsaturated fatty acids, and polyphenols. [12] The potential health benefits of microalgae and their respective bioactive compounds include anti-oxidant, anti-cancer, anti-inflammatory, and immunomodulatory aspects. [13,14] According to earlier published results, microalgae and their bioactive compounds have the potential for neuroprotection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10,11] Microalgae are considered a high-quality nutritional source for human health due to their abundant primary and secondary bioactive metabolites, such as polypeptides, lipids, vitamin polyunsaturated fatty acids, and polyphenols. [12] The potential health benefits of microalgae and their respective bioactive compounds include anti-oxidant, anti-cancer, anti-inflammatory, and immunomodulatory aspects. [13,14] According to earlier published results, microalgae and their bioactive compounds have the potential for neuroprotection.…”
Section: Introductionmentioning
confidence: 99%
“…The marine environment has been revealed to be an interesting source of new active substances with great pharmacological potential [10,11] . Microalgae are considered a high‐quality nutritional source for human health due to their abundant primary and secondary bioactive metabolites, such as polypeptides, lipids, vitamin polyunsaturated fatty acids, and polyphenols [12] . The potential health benefits of microalgae and their respective bioactive compounds include anti‐oxidant, anti‐cancer, anti‐inflammatory, and immunomodulatory aspects [13,14] .…”
Section: Introductionmentioning
confidence: 99%
“…Bioactive substances that are present in nature generally have powerful physiological or pharmacological effects, such as curcumin [ 4 ], tocopherols [ 5 ], flavonoids [ 6 ], resveratrol [ 7 ], anthocyanins [ 8 ], puerarin [ 9 ], ferulic acid [ 10 ], and carvacrol [ 11 ], which are not essential for maintaining human growth and development but have significant health benefits [ 12 ]. Recent research has shown that bioactive substances have plenty of functions—such as antioxidant [ 13 ], anti-inflammatory [ 14 ], antibacterial [ 15 ], anticancer, and immunomodulatory [ 16 , 17 ] functions—and play an important role in health maintenance, disease prevention, and physiological function regulation. However, owing to their physicochemical properties, most bioactive substances are environmentally sensitive, unstable to light and heat, easily damaged or degraded, structurally altered, thus reducing or losing their activity, and have low bioavailability [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The miRNA is then degraded, cleaved, or mediated by translational stimulation. Fucoxanthin has been shown to decrease levels of mir-146b expression[230].…”
mentioning
confidence: 99%